"Panhilo" a case study on its victims in Leyte - Burgos, Gamaliel Roy E. (1998)
The study was composed of ten victims who were interviewed about their experiences of being poisoned. The purpose of this was to get their individuals perspective regarding the concept of the practice. The result of the study shows that they learned some of the information regarding the practice because it was explained to them by the "tambalan" after their treatment process, while some of them said that they were informed through their friends, relatives and neighbors. With the researcher's hypothesis, it was found out that the effect of the practice on the victims and the purposes and methods used in doing the "panhilo" would depend on the choice of the "manghihilos" themselves.